LIPID COMPOSITION OF CALICOPHORON PAPILLOSUM AND PARAMPHISTOMUM EPICLITUM (TREMATODA: PARAMPHISTOMIDAE) FROM CATTLE - GOYAL, K. C.; GANDH, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Total lipids and their different fractions have been determined in two amphistomid parasites, Calcophoron papillosum and Paramphistomum epiclitum, collected from the runnen of buffaloes, Bubalus bubalis. Among the fractional lipids free fatty acids have been found to be in highest concentration and glycolipids in the lowest concentration. Phospholipids and glycolipids are present approximately in similar amounts. Both the parasites have been collected from the same host at the same time in Chandigarh.